Capacity of nurses and midwives for early identification of developmental delays among children in a Ghanaian rural district - Hasehni Vampere; Wisdom Kwadwo Mprah; Enoch Acheampong; Emmanuel Appiah-Brempong; Joseph Jenkins Mensah (Cogent Public Health, 2023)
Abstract: Early identification of developmental delays provides an opportunity for early intervention that improves the child’s growth and development. Primary healthcare providers have a basic responsibility for the early identification of developmental delays for intervention or referral to the appropriate specialist. However, the capacity of primary healthcare providers to identify children with developmental delays in the Wa West District of Ghana is unknown. A cross-sectional study was conducted involving 113 primary healthcare providers working in various healthcare facilities in the Wa West district. The participants were obtained through a simple random sampling technique. Quantitative data were collected using a structured questionnaire and analyzed using descriptive statistical analysis. The results indicated that 87 (77.0%) participants found their training adequate for early identification of developmental delays. However, less than 10% of the participants reported having excellent knowledge on the use of tools for early identification. While an average of 77.1% of the participants showed knowledge in the areas of a child’s medical history-taking, the diet of the child 65 (57.5%) was cited as least important. Also, an average of 67.6% of participants responded accurately to questions seeking their knowledge on screening. However, few 30 (26.5%) participants knew that not all screening results are always accurate. Higher education and work experience appear influential on participants’ knowledge on various areas of early identification of developmental delays. In conclusion, gaps in participants’ knowledge on areas of early identification of developmental delays could lead to late identification, hence limiting the child’s development and outcome of intervention services.